Best practices for the implantation of ISO 14001 norms: a study of change management in two industrial companies in the Midwest region of the state of São Paulo - Brazil - de Oliveira, Otavio Jose [UNESP]; Muniz Serra Pinheiro, Camila Roberta [UNESP] (Elsevier B.V., 2009)
Among the difficulties found in the implementation of ISO 14001 systems, resistance to change can always be found. It is mainly a consequence of the hurry to change, loss of focus, concentration of decision making at the level of top management, arbitrary imposition of objectives and results, faulty communication, and the absence of motivational and financial incentive for change.Therefore, the main objective of this paper is to present best practices with respect to the management of organizational change due to the implementation of ISO 14001 norms in two industrial companies in the Midwest region of the State of São Paulo - Brazil. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Environmental management; ISO 14001; Resistance to change; Personnel management